Comparison of the Use of NaOH and KOH Activators in the Manufacture of Activated Carbon from Cassava Peel (Manihot utilissima) - Mitha Puspitasari; Wibiana Wulan Nandari; Faizah Hadi (Eksergi, 2022)
Cassava (Manihot utilissima) is a staple food beside rice and corn for Indonesia people. Cassava peel is a waste of cassava processing agroindustries such as  tapioca flour industry, fermentation industry, and staple food industry. This waste contains a fairly high carbon element of 59,31%. Cassava peel has the potential to be used as raw material for activated carbon because of its high carbon content. Activated carbon production involved some steps such as preparing raw materials, carbonization, activation, neutralization, and analysis of water content, ash, iodine number, and analysis of the pore surface area of activated carbon. Activated carbon was activated using NaOH and KOH with concentrations of 0.1; 0,2; 0,3; 0,4; and 0,5N. The results showed that activated carbon which activated with 0,4N NaOH and 0,5N KOH provided the closest parameter with SNI 06-3730-1995 standard. The use of NaOH activator can increase the surface area of activated carbon compared to KOH activator.